Reuse and renovation in Roman material culture functions, aesthetics, interpretations - Swetnam-Burland, Molly; Ng, Diana Y. (New York, NY Cambridge University Press, 2018)
"This book explores the spoliation of architectural and sculptural materials during the Roman empire. Examining a wide range of materials, including imperial portraits, statues associated with master craftsmen, architectural moldings and fixtures, tombs and sarcophagi, arches and gateways, it demonstrates that secondary intervention was common well before Late Antiquity, in fact, centuries earlier than has been previously acknowledged. The essays in this volume, written by a team of international experts, collectively argue that reuse was a natural feature of human manipulation of the physical environment, rather than a sign of social pressure. Reuse often reflected appreciation for the function, form, and design of the material culture of earlier eras. Political, social, religious, and economic factors also contributed to the practice. A comprehensive overview of spoliation and reuse, this volume examines the phenomenon in Rome and throughout the Mediterranean world."--
1. 'The reuse and redisplay of honorific statues in Pompeii' Brenda Longfellow-- 2. 'The Vigiles, dynastic succession and symbolic reappropriation in the Caserma dei Vigili at Ostia' Margaret L. Laird-- 3. 'The epigraphy of appropriation: retrospective signatures of Greek sculptors in the Roman World' Catherine M. Keesling-- 4. 'Gateways to the past: the Hadrianic architecture of procession in Pisidian Antioch and Athens' Adrian J. Ossi-- 5. 'Visual literacy and reuse in the architecture of late Imperial Rome' Elisha Ann Dumser-- 6. 'Urban transformations at Aphrodisias in Late Antiquity: destruction or intentional preservation?' Esen Ogus-- 7. 'Acquiring the antique in Byzantine Rome: the economics of architectural reuse at Santa Maria Antiqua' Gregor Kalas-- 8. 'The afterlife of the amphitheater: cultural biography and social memory at Tarragona' Sheila Bond.--
Originated in a panel, Afterwards: Art and Architecture as Iterative Practice in the Roman World, presented at the meetings of the College Art Association in 2014
Includes bibliographical references and index
Keywords: Aesthetics, Roman; Architecture, Roman; Sculpture, Roman; Material culture -- Rome; Building materials -- Recycling -- Rome; Sculpture materials -- Recycling -- Rome